2002
DOI: 10.1021/ac010067k
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Mitoxantrone by Surface-Enhanced Resonance Raman Scattering

Abstract: Mitoxantrone is an anticancer agent for which it is important to know the concentration in blood during therapy. Current methods of analysis are cumbersome, requiring a pretreatment stage. A method based on surface-enhanced resonance Raman scattering (SERRS) has been developed using a flow cell and silver colloid as the SERRS substrate. It is simple, sensitive, fast, and reliable. Both blood plasma and serum can be analyzed directly, but fresh serum is preferred here due to reduced fluorescence in the clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 51 publications
0
68
0
2
Order By: Relevance
“…Raman spectroscopy is more often associated with the determination of molecular structure and with qualitative analysis; as an example, the conformational characterisation of natively unfolded proteins through a simple band fitting of the amide I region has been recently described (Maiti et al, 2004). There have also been numerous applications of Raman spectroscopy for the quantitative analysis of sample composition, the most relevant application fields being clinical (Mc Laughlin et al, 2002;Pelletier, 2003). It needs further studies to unravel all the information or data present in the Raman spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…Raman spectroscopy is more often associated with the determination of molecular structure and with qualitative analysis; as an example, the conformational characterisation of natively unfolded proteins through a simple band fitting of the amide I region has been recently described (Maiti et al, 2004). There have also been numerous applications of Raman spectroscopy for the quantitative analysis of sample composition, the most relevant application fields being clinical (Mc Laughlin et al, 2002;Pelletier, 2003). It needs further studies to unravel all the information or data present in the Raman spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…In, particular when the analyte has a high Raman cross-section compared to other species in a sample matrix the analyte can be identified directly due to its molecularly specific spectrum, enabling sample identification with no separation steps. 45 Because most SERS enhancement comes from the first layer on the metal surface, the amount of sample added should be such as to allow sample adsorption without steric crowding or multilayer adsorption. This can be counterintuitive.…”
Section: Quantitative Applicationsmentioning
confidence: 99%
“…[11][12][13] Higher local resolution can be obtained by combining the SERS technique with an AFM [known as tip-enhanced Raman spectroscopy (TERS)] [14] or glass fibre probes. [15] Possible applications of a reproducible SERS approach are 1) the determination of drug concentrations in blood plasma or risky additives in food, [16] 2) the detection and identification of microbial contaminants, [17] and 3) DNA detection in microorganisms. [18] For the application of the SERS technique in bioanalytical or pharmaceutical devices, [19] reproducible signal intensity must be guaranteed for several analytes over long measuring periods or across measuring areas of several square microns.…”
Section: Introductionmentioning
confidence: 99%
“…Our group recently showed that a promising way to achieve reproducible SERS signals over a long measuring period is by combining a microfluidic channel system with the SERS technique using metallic nanoparticles as SERS-active substrates. [16,20,21] Herein, the preparation and testing of highly reproducible array-like SERS-active substrates are introduced. According to calculations, large enhancement factors require metallic nanoparticles or structures with sharp or needle-like edges.…”
Section: Introductionmentioning
confidence: 99%